2006
DOI: 10.1890/03-5410
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Scale Affects Community Concordance Among Fishes, Benthic Macroinvertebrates, And Bryophytes In Streams

Abstract: Owing to the lack of information about the distribution patterns of many taxonomic groups, biodiversity conservation strategies commonly rely on a surrogate taxa approach for identifying areas of maximum conservation potential. Macroinvertebrates or fish are the most likely candidates for such a role in many freshwater systems. The usefulness of the surrogate taxa depends largely on community concordance, i.e., the degree of similarity in community patterns among taxonomic groups across a set of sites. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
101
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 38 publications
11
101
1
3
Order By: Relevance
“…Fish are more abundant in larger rivers than in smaller ones. This typical pattern has been explained in terms of habitat diversity (Gorman and Karr, 1978;Paavola et al, 2006), differences of mobility and extinction, stream size (Paavola et al, 2006), or sampling phenomena (Angermeier and Schlosser, 1989). It might also be influenced by available food resources, which are limited in the upper regions of streams.…”
Section: Discussionmentioning
confidence: 99%
“…Fish are more abundant in larger rivers than in smaller ones. This typical pattern has been explained in terms of habitat diversity (Gorman and Karr, 1978;Paavola et al, 2006), differences of mobility and extinction, stream size (Paavola et al, 2006), or sampling phenomena (Angermeier and Schlosser, 1989). It might also be influenced by available food resources, which are limited in the upper regions of streams.…”
Section: Discussionmentioning
confidence: 99%
“…Can fish or macroinvertebrate assemblages individually sufficiently represent the effects of anthropogenic stressors on river communities alone? Several studies (Griffith et al 2005;Paavola et al 2006;Flinders et al 2008;Infante et al 2009;Walters et al 2009;Bedoya et al 2011;Marzin et al 2012;Neff & Jackson 2013;Johnson & Ringler 2014;Pili ere et al 2014) that have compared the sensitivity of fish-and macroinvertebrate-specific indices in identifying main stressors suggest that two assemblages should be used simultaneously in bioassessment. Our analysis suggested that the screened metrics for fish and macroinvertebrates responded differently to the various environmental stressors.…”
Section: Metric Response To Environmental Degradationmentioning
confidence: 99%
“…Despite the recommendations for assessments using fish and macroinvertebrate assemblages, less than a dozen studies (Griffith et al 2005;Paavola et al 2006;Flinders et al 2008;Infante et al 2009;Walters et al 2009;Bedoya et al 2011;Marzin et al 2012;Neff & Jackson 2013;Johnson & Ringler 2014;Pili ere et al 2014) have compared the responses of fish and macroinvertebrate assemblage-specific indices to stressors and suggested two taxonomic assemblages together are needed to determine streams and rivers condition. For example, Johnson and Ringler (2014) suggested that the major environmental variables affecting fish and macroinvertebrate assemblages differed, macroinvertebrate metrics better responded to substrate composition and land use, whereas stream morphometry and water chemistry were important variables for fish metrics, which was consistent with Walters et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, lake communities may be more controlled by deterministic processes at larger spatial scales, while pond communities may be more influenced by stochastic factors at ecological time scales, as many ponds experience cyclic periods of drought (Chase, 2007). These scale-related changes can alter the concordance between the freshwater biotas of several groups (Paavola et al, 2006). We thus believe that research on lentic communities from a macroecological perspective will benefit from considering the size-scaling between ponds and lakes explicitly in the analyses, at least for organisms inhabiting both types of habitats.…”
Section: Introductionmentioning
confidence: 99%